Анімація графічних об’єктів у технології захоплення рухів - Павлова, М. О. (ХНУРЕ, 2019)
Describes the implementation options technology "motion capture" for the implementation of animation in computer graphics. This technology provides movements of physically moving objects, which is displayed in computer models. It provides the ability to accurately study the movement of a person and apply it in computer graphics.